The hunted [videorecording (DVD)] - Griffiths, David, (Screenwriter); Griffiths, Peter, 1950-; Monterastelli, Art; Jones, Tommy Lee, 1946-; Toro, Benicio del, 1967-; Nielsen, Connie, 1965-; Stefanson, Leslie, 1971-; Finn, John, 1952-; Zúñiga, José; Canada, Ron; Deschanel, Caleb, 1944-; Tyler, Brian (Composer) (Paramount, 2021)
An FBI deep-woods tracker captures a trained assassin who has made a sport of hunting humans.